a Prototype Design of Smart Quranic Garden System using ATmega328 and ESP8266 Microcontrollers - Anggara, Muhamad Rafi; Disbuhadi, Andi (Perhimpunan Intelektual Muslim Indonesia, 2022)
Medicinal plants are a significant agricultural commodity cultivated by farmers in Parongpong District, West Bandung Regency, with the bidara plant (Ziziphus mauritiana) being a primary focus of the Quran Garden Foundation. In addition to its health benefits, bidara cultivation aligns with Islamic teachings, making it a valuable resource for wellness and religious practice. This study aims to develop and test a Smart Quranic Garden System prototype based on greenhouse automation technology and Internet of Things (IoT) security using ATmega328 and ESP8266 microcontrollers to optimize bidara plant growth. The research employed an experimental design to create and test systems for automated watering, weather control, and security. The prototype integrates sensors and actuators to automate these processes and enhance cultivation efficiency. Testing revealed that the watering system activates the pump when the soil moisture sensor detects an ADC value of 700 or higher. For the weather control system, the heater activates when the DHT11 sensor detects temperatures below 25°C, and the blower operates when temperatures exceed 30°C. The security system responds effectively, with the solenoid lock opening only when the correct password is entered and the virtual button on the Blynk application is pressed. This prototype demonstrates the potential for implementation in optimizing the growth of bidara plants in Parongpong District by improving cultivation efficiency and security, contributing to sustainable agricultural practices and supporting the Quran Garden Foundation's vision.